Long Suffering Relationship to Self Management Behavior and Complications in Type 2 Diabetes Mellitus Sufferers - Ulfa, Hana Zumaedza; Wardoyo, Eko; Dijaya, Jelita Intan (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus is a long-term chronic disease and has a high risk of complications. So to prevent complications, continuous self-management is needed. This will affect the success of preventing complications in DM patients, especially those who have been diagnosed for a long time. The purpose of this study was to determine the relationship between the duration of suffering and self-management behavior and disease complications in type 2 DM patients. This research method is quantitative research with a cross-sectional approach. The population of this study was 85 respondents with a research sample of 67 respondents. The research sample was taken using purposive sampling technique. The study was conducted in the Bunut Health Center Work Area in July 2024. Data were analyzed using the Chi-Square test. The results of the study showed that there was a relationship between the duration of suffering and self-management behavior with a p-value of 0.001 (<0.05), and there was a relationship between the duration of suffering and disease complications with a p-value-value≤0.001 (<0.05). The conclusion of this study is that the longer a patient suffers from diabetes mellitus, the more it will affect the patient's motivation in carrying out self-management, which will have an impact on increasing glycemic status which will have an impact on the occurrence of disease complications.